HEALTH EDUCATION STRATEGY TO IMPROVE COMMUNITY KNOWLEDGE ON DENGUE PREVENTION IN EAST SIDOMULYO VILLAGE - Mardinah, Shaffa; Niken Yuniar Sari; Sri Minarni; Ichwanul Alif Ramadhan; Wardatul Uyuni; Ismi Amin; Christina Rajagukguk; Alisia Oktaviani Marito Siahaan; Berry Waldain; Nabila Oktaviani Azhar; et al. (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2025)
Dengue Hemorrhagic Fever (DHF) remains a serious public health concern in Indonesia, especially in densely populated urban areas. Lack of knowledge regarding prevention and symptom recognition increases the risk of outbreaks. This community service activity aimed to improve public knowledge and attitudes toward DHF prevention in RW 08 East Sidomulyo Village, Pekanbaru. Methods included interactive health education sessions with pre–post evaluation involving 25 participants selected through simple random sampling. The results showed a significant increase in participant awareness; knowledge improved from 60% in the low category to 92% in the good category after the intervention. This demonstrates that structured health education is effective in enhancing public understanding of DHF prevention through the "3M Plus" program and early symptom recognition.